2014
DOI: 10.3892/ol.2014.2670
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis is a strong predictor for recurrence in patients with pathological T1a renal cell carcinoma

Abstract: Patients with pT1aN0M0 renal cell carcinoma (RCC) generally have good prognosis, and recurrence is rare. However, metastasis develops postoperatively in a small number of patients with pT1aN0M0 RCC. The present study was undertaken to identify predictors for recurrence in patients with pT1aN0M0 RCC. We reviewed the clinicopathological factors of 133 patients with pT1aN0M0 RCC who underwent radical or partial nephrectomy at the Department of Urology, National Defense Medical College (Saitama, Japan). Clinicopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…The presence of tumor necrosis is a well-established independent indicator of a poor prognosis for RCC, and presence of necrosis results in higher ADC values [18,19]. In our study, there was a statistically significant positive correlation between the ADC values and tumor necrosis.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The presence of tumor necrosis is a well-established independent indicator of a poor prognosis for RCC, and presence of necrosis results in higher ADC values [18,19]. In our study, there was a statistically significant positive correlation between the ADC values and tumor necrosis.…”
Section: Discussionsupporting
confidence: 64%
“…So, further studies with larger patient populations are warranted [18]. The number of cells is a crucial indicator of tumor grade [19]. It has been suggested that the decreased ADC value may be due to their increased cellularity, larger nuclei with more abundant macromolecular proteins, and less extracellular space [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…TNM stage was assigned according to the 2010 AJCC TNM classification [ 3 ]. Tumor necrosis was defined as microscopic coagulative necrosis [ 26 ]. Lymphovascular invasion was defined as tumor cell invasion of blood vessels or lymphatic vessels, but not the underlying muscular walls [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…They analyzed data from 133 patients who underwent RN or PN, comparing the clinico-pathological characteristics of patients with or without recurrence. They found that tumor size and the percentage of tumor necrosis significantly differed between the 2 groups and were confirmed as predictors of recurrence at univariate analysis [49]. Based on these data, the presence of necrosis should be considered to optimize the follow-up of patients with SRMs, although these findings should be confirmed in prospective trials.…”
Section: Srms: Growth Risk Of Recurrence and Metastasismentioning
confidence: 88%